IMPLEMENTASI SMS GATEWAY BERBASIS WEB PADA KOPERASI SIMPAN PINJAM PT. SUCOFINDO MAKASSAR - Ida (PROGRESS, 2018)
The use of cellular telephones based on SMS (Short Message Service) is present to provide convenience for the public against a problem solved. By using this SMS facility, an SMS-based loan and customer payment information system application can be built. The choice of communication technology in the form of SMS is because it is more practical, inexpensive and efficient for conveying information. The purpose of this study is to design and implement an SMS gateway-based application to improve the quality of service to customers and help smooth the savings and loan cooperative system. The stage of designing and implementing the SMS Gateway Application as Customer Information media using the waterfall method. Consisting of the stages of analysis, design, coding, testing, implementation and maintenance. This SMS-based customer information service serves to provide loan information and customer payments for the predetermined SMS format. The SMS Gateway application is built using three main components, namely Gammu as a special software for SMS Gateway, PHP as a programming language, and MySQL as a database server. From the results of trials using the Huawei CE0682 GSM modem, this SMS Gateway application can function properly. the customer sends an SMS, then the system will send a reply SMS in accordance with the format of the SMS sent.